IMU Sensor Based Home Search Method Using Backtracking Algorithm on Hexapod Robot in Indonesia Fire Extinguisher Robot Contest - Maydevanti, Yesa Friti; Widodo, Nuryono Satya (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
Abstract-This paper describes the IMU sensor-based home search using a backtracking algorithm on a hexapod robot in the Indonesian fire fighting robot contest. The search for the homepage in this Indonesian legged robot contest is part of the robot's mission to achieve maximum points in the race. The algorithm discussed in this paper is a backtracking algorithm. Where the robot will return to the initial position by tracing solutions that meet the requirements. By using the IMU BNO055 sensor the robot will follow the direction that will depart then will guide the robot back to its home position. The results show that the backtracking algorithm is successfully implemented. So that the robot will still return home even though an error occurs when crossing the room intersection.